Vibrational density of states of rare-gas crystal doped with impurities. - Frigerio, A.; Bonadeo, H.; Weissmann, M.; Cohan, N. V. (American Physical Society, 1983)
Fil: Frigerio, A. Comisión Nacional de Energía Atómica; Argentina